Small bowel obstruction complicating an Ascaris lumbricoides infestation in a 4-year-old male: a case report - Clarence Mvalo Mbanga; Kingsley S. Ombaku; Karl Njuwa Fai; Valirie Ndip Agbor (Journal of Medical Case Reports, 2019)
Abstract Background Ascariasis is the leading helminthic infection worldwide, with its peak prevalence noted in children aged 2–10 years. Although mainly asymptomatic, chronic and heavy infestation could lead to severe complications such as malnutrition, poor physical and cognitive development, as well as intestinal obstruction. We report the case of a 4-year-old boy with intestinal obstruction due to Ascaris lumbricoides infestation and discuss its public health significance. Case presentation A 4-year-old Black African boy from the Menchum Division in the Northwest Region of Cameroon, with no history of deworming since birth, presented with a 3-day history of generalized abdominal pains, vomiting and obstipation, and abdominal distention evolving over a period of 6 months. Clinical and paraclinical findings were in favor of a subacute intestinal occlusion associated with an electrolyte imbalance. An exploratory laparotomy was done after correction of the electrolyte imbalance. Perioperative findings revealed a dilated small bowel obstructed by bundles of live worms. An enterotomy of 2 cm in length was done, and the bundles of Ascaris lumbricoides worms extracted manually and by milking through the stoma. His postoperative period was unremarkable, and he was discharged on postoperative day 7. He and his entire household were dewormed with a single dose of mebendazole 500 mg administered orally. A follow-up visit 1 week after discharge revealed a healed abdominal wound and normal bowel functions. Conclusion Despite considerable progress made on the control of soil-transmitted helminthiasis in Cameroon, the program faces a number of bottlenecks. Funding is inadequate, making data acquisition and hence remapping of high-risk zones difficult. Accessibility to enclaved zones where most high-risk children live is difficult, while community sensitization on soil-transmitted helminthiasis and proper education on the right environmental hygienic practices are lacking. All these challenges once addressed could go a long way to help achieve recently set sustainable development goals.